1959
DOI: 10.2105/ajph.49.7.903
|View full text |Cite
|
Sign up to set email alerts
|

The Ultraviolet Irradiation of Biological Fluids in Thin-Flowing Films

Abstract: This study is concerned with the use of ultraviolet irradiation for sterilizing or inactivating viruses and bacteria in biological fluid preparations. Of special interest for public health are a discussion of the biological effectiveness of ultraviolet irradiation of fluids, and a description of an apparatus for uniform exposure of microthin films to irradiation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0
1

Year Published

1963
1963
2013
2013

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(7 citation statements)
references
References 20 publications
0
6
0
1
Order By: Relevance
“…By 1955, this was abandoned following a fairly careful dem onstration showing that efficacious sterilisation of plasma could only be achieved by dosages of radiation that inacti vated serum components [23,24], However, it has been suggested that the early studies might not have been that accurate, and often more than one wavelength was used. More recent work suggests that a process for eliminating some viruses might be attainable based on values for ret rovirus inactivation and FVIII activity [24], This optimis tic view of UV irradiation persists and various thin-layer forming devices continued to be evaluated [25], The UV irradiation continues to offer a process which requires no addition of chemicals or photodynamic agents, such as psoralens [26] or ß-propiolactone [27], It is also reason ably rapid for selected virus groups especially singlestranded nucleic acids which show less resistance to UV radiation [24], HIV can be inactivated by UV irradiation at doses of 10,000 J/m2 [28] when a UV wavelength of 254 nm (UVC) was used and it was found that 2 logs of HIV could be inactivated by UV at the dose of 5,000 J/m2 [29]. Also recent investigation of gamma radiation would suggest that UV still remains a better alternative for a well-defined and selected process.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…By 1955, this was abandoned following a fairly careful dem onstration showing that efficacious sterilisation of plasma could only be achieved by dosages of radiation that inacti vated serum components [23,24], However, it has been suggested that the early studies might not have been that accurate, and often more than one wavelength was used. More recent work suggests that a process for eliminating some viruses might be attainable based on values for ret rovirus inactivation and FVIII activity [24], This optimis tic view of UV irradiation persists and various thin-layer forming devices continued to be evaluated [25], The UV irradiation continues to offer a process which requires no addition of chemicals or photodynamic agents, such as psoralens [26] or ß-propiolactone [27], It is also reason ably rapid for selected virus groups especially singlestranded nucleic acids which show less resistance to UV radiation [24], HIV can be inactivated by UV irradiation at doses of 10,000 J/m2 [28] when a UV wavelength of 254 nm (UVC) was used and it was found that 2 logs of HIV could be inactivated by UV at the dose of 5,000 J/m2 [29]. Also recent investigation of gamma radiation would suggest that UV still remains a better alternative for a well-defined and selected process.…”
Section: Introductionmentioning
confidence: 99%
“…More ieccnt work suggests that a process for eliminating some vir~ises might be attainable based on values for retrovirur inactivation and FVlII activity [24]. This optimistic view o f UV irradiation persisls and various thin-layer forming devices continued to be evaluated [25]. The UV irradiation continues to offer a process which requires no addition of chemicals or photodynamic agents, such as psoralcns [26] or fi-propiolactone [27].…”
Section: Introductionmentioning
confidence: 99%
“…One ml. treated saliva was inoculated into [15][16][17][18][19][20] ml. broth and incubated aerobically at 370 C. for 72 hours before results were recorded.…”
mentioning
confidence: 99%
“…19 Briefly, this instrument-the "Centrifilmer"-consists of a rotating conical stainless-steel bowl of large volume in which is suspended an ultraviolet lamp unit, consisting of six special glass# or quartz tubes. Liquids to be sterilized are exposed to the radiation as they flow up the sides of the rotating bowl.…”
mentioning
confidence: 99%
“…The strain pool samples were obtained, as noted, from actual vaccine production processing steps. The adenovirus vaccine inactivation process is a three-phase process in which the filtered virus suspension is treated with formaldehyde at a concentration of 0.031 M, incubated at 37 C for 48 hr (in two steps), subjected to 25 incident watts of ultraviolet (UV) light in a Centriffilmer (25), and, finally, treated for another 4 hr at 37 C with j3-propiolactone (BPL) at a final concentration of 0.014 M. This procedure and individual phases of it were duplicated experimentally and used on the type 12 and type 7 (Pinckney) adenovirus and SV-40 preparations. Specific parts of the inactivation procedure were evaluated by testing experimentally prepared samples.…”
Section: Methodsmentioning
confidence: 99%